Indonesia’s Online Vacancy Outlook : From Online Job Postings to Labor Market Intelligence 2020 - World Bank (World Bank, Washington, DC, 2022)
The objective of this technical report and the accompanying skills profiles report is twofold. First, the technical report explains the methodology used to transform job postings text into OV data and in turn, illustrates how to use those data to produce labor market intelligence valuable to different users. Second, the report presents answers to questions often asked by end-users and policymakers. This work is part of a series produced by the World Bank to support the Government of Indonesia in strengthening its labor market information system (LMIS). The OVO presents the results of one of four data pilots that, if adopted by the government, will provide the information needed to fill in important data gaps and to provide key labor market intelligence services to different users. Moreover, while this work focuses on the Indonesian context, it may also inform decisions in other developing countries that are considering the utilization of these data and having concerns about their validity when there is limited access to the internet and widespread informality.